PENGARUH ETOS KERJA ISLAM TERHADAP KINERJA KARYAWAN DENGAN KEADILAN ORGANISASIONAL DAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL INTERVENING (Studi pada Perawat Tetap Rumah Sakit Islam Sultan Agung Semarang) - Sari, Intan Permata; Nugraheni, Rini (Faculty of Economics and Business Diponegoro University, 2019)
The purpose of this study is to determine and analyze the influence of Islamic work ethic towards employee performance with organizational justice and organizational commitment as mediators. In this study, both primary and secondary data wereobtained. Secondary data were collected from various sources, such as journals, books and data obtained from the company, while primary data by usingquestionnaire.To measure the variables, it was used questionnaires distributed to 96 employees working in RSI Sultan Agung Semarang based on purposive sampling method. The techniquesof data analysis that used in this study is Partial Least Square using SmartPLS 3.2.8software to determine the path coefficient, the indirect influence ofexogenous variables on endogenous variables.Findings shows that, the Islamic work ethic has a positive and significant effect towards the organizational justice and organizational commitment. Organizational justice and organizational commitment also have a positive and significant effect on employee performance.In addition, it is shown that organizational justice and organizational commitment proved tomediate the relationship between Islamic work ethic toward employee performance. Among organizational justice and organizational commitment is the most powerful in mediating the relationship between the Islamic work ethic and employee performance, namely organizational commitment.